2011
DOI: 10.1177/1029864911423164
|View full text |Cite
|
Sign up to set email alerts
|

Restraint of body movement potentially reduces peak SPL in western contemporary popular singing

Abstract: In western contemporary popular (WCP) singing, body movement is integral to overall stage performance. However, singers are often directed to stand still while singing during recording sessions or music theatre productions. No assessment has been undertaken by sound engineers or directors to determine whether singers can produce the same sound levels under conditions of voluntary movement restraint. The aim of this investigation was to assess the impact of body movement restraint on sound pressure levels (SPL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Further, our expectation that SPL range in the NM condition would be reduced compared with the movement condition was also not supported. Possible explanations for the reductions in peak SPL under the conditions of movement restriction were covered in detail in our previous paper (Turner & Kenny, 2011). These results indicated that movement restriction is associated with the reduction of overall SPL not just SPL peaks.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Further, our expectation that SPL range in the NM condition would be reduced compared with the movement condition was also not supported. Possible explanations for the reductions in peak SPL under the conditions of movement restriction were covered in detail in our previous paper (Turner & Kenny, 2011). These results indicated that movement restriction is associated with the reduction of overall SPL not just SPL peaks.…”
mentioning
confidence: 69%
“…This allowed singers to maintain a consistent dynamic difference in SPL throughout the song. This also meant that even though the same singers in our previous study had significant reductions in peaks (Turner & Kenny, 2011) this was compensated for in terms of maintaining the dynamic variation by an equivalent reduction in minimum SPL.…”
Section: Assessment Of Statistical Differencesmentioning
confidence: 89%
See 1 more Smart Citation
“…Musicians, although very familiar with Western musical conventions such as staff notation, are expected to be better at "escaping" the language-congruent vertical mapping that might have detrimental effects on the singing quality if gestures start to regulate suboptimal tension in the vocal apparatus (cf. Turner and Kenny, 2011). The directionality of the participants' head movements during their singing performances was computed using the vertical movement trajectories of the nose as tracked by the OpenPose (Cao et al, 2017) algorithm.…”
Section: Discussionmentioning
confidence: 99%